Using VLOOKUP in Microsoft Excel or Google Spreadsheet / Lim Teck Heng - Lim, Teck Heng (Academy of Language Studies, 2022)
Ctrl+F is a keyboard shortcut that many of us are familiar with. We usually use it to find words or phrases quickly and efficiently when reading or browsing through an article on a website. We can also use it in word processing programs, spreadsheets, or even PDFs. Though Ctrl+F allows us to find specific data in Microsoft Excel and Google Spreadsheets, its usefulness stops there as we could not manipulate the data any further. In this short article, we will look at how to use VLOOKUP to find and display a particular data when using spreadsheets programs such as Microsoft Excel or Google Spreadsheet. Let’s start by looking at the syntax Syntax: =VLOOKUP(lookup_value, table_array, col-index-num, rangejookup)